Aphrastomedes anthocoroides, a remarkable new cimicomorphan genus and species (Hemiptera: Heteroptera) from Upper Cretaceous Burmese amber. (April 2018) - Yamada, Kazutaka; Yamamoto, Shûhei; Takahashi, Yui
Abstract: A new genus and species of cimicomorphan bug, Aphrastomedes anthocoroides Yamada and Yamamoto, gen. and sp. nov., is described and illustrated based on two specimens preserved in Upper Cretaceous (Cenomanian) amber from the Hukawng Valley of northern Myanmar (Burma). This remarkable cimicomorphan species is tentatively assigned to the family Velocipedidae primarily on the basis of the structure of the labium, forewings, and genitalia. Aphrastomedes is considered best placed in the Cimiciformes as a member of the Velocipedidae, and it also has a close relationship to the Medocostidae.